A miRNA181a/NFAT5 axis links impaired T cell tolerance induction with autoimmune type 1 diabetes - Serr, Isabelle; Scherm, Martin G.; Zahm, Adam M.; Schug, Jonathan; Flynn, Victoria K.; Hippich, Markus; Kaelin, Stefanie; Becker, Maike; Achenbach, Peter; Nikolaev, Alexei; Gerlach, Katharina; Liebsch, Nicole; et al. (Science Translational Medicine, 2018)
Molecular checkpoints that trigger the onset of islet autoimmunity or progression to human type 1 diabetes (T1D) are incompletely understood. Using T cells from children at an early stage of islet autoimmunity without clinical T1D, we find that a microRNA181a (miRNA181a)-mediated increase in signal strength of stimulation and costimulation links nuclear factor of activated T cells 5 (NFAT5) with impaired tolerance induction and autoimmune activation. We show that enhancing miRNA181a activity increases NFAT5 expression while inhibiting FOXP3+ regulatory T cell (T-reg) induction in vitro. Accordingly, Treg induction is improved using T cells from NFAT5 knockout (NFAT5ko) animals, whereas altering miRNA181a activity does not affect T-reg induction in NFAT5ko T cells. Moreover, high costimulatory signals result in phosphoinositide 3-kinase (PI3K)-mediated NFAT5, which interferes with FoxP(3+) Treg induction. Blocking miRNA181a or NFAT5 increases Treg induction in murine and humanized models and reduces murine islet autoimmunity in vivo. These findings suggest targeting miRNA181a and/or NFAT5 signaling for the development of innovative personalized medicines to limit islet autoimmunity.
EVALuna2:33886